Pengaruh Pendidikan, Pelatihan, dan Pengembangan Karier Terhadap Kinerja Guru pada Sekolah Menengah Atas Al Falah Sumber Gayam Kadur Pamekasan Madura - Umam, Mohammad Khairul (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2020)
This study aims to determine "The Influence of Education, Training and Career Development on Teacher Performance at Al-Falah Secondary School Sumber Gayam Kadur Pamekasan Madura". windows 17.00. The population in this study were teachers at Al Falah Senior High School, Sumber Gayam Kadur Pamekasan. A total of 21 respondents, because of the available population of 21 teachers as respondents, all of the population was at once a member of the sample, and henceforth this study was called population research. The results of the study Based on the results of the questionnaire/questionnaire to 21 respondents, the following multiple linear regression equation was obtained: Y = 0.139 + 0.358 X1 + 0.154 X2 + 0.699 X3 From the regression equation it can be explained that X1 Education, X2 Training, and X3 Development have an influence on teacher performance at  High School Of High School Al Falah Sumber Gayam Kadur Pamekasan (Y). Simultaneous hypothesis testing (F test) shows F_count 12.63 > F_table 3.07 which means that the independent variables are education X1, Training X2, and career development X3, together (simultaneously) have a significant effect on the dependent variable (Y), namely teacher performance. at High School Of High School Sumber Gayam Kadur Pamekasan. Partial hypothesis test (t test) shows education X1, obtained t¬_ count, 1.995 > t, table 0.686. X2 training obtained t_count 0.857 > t_table 0.686. The influence of career X3 is obtained t_count 5.175 > t, table 0.686, which means that career development X3 is the most dominant in influencing teacher performance (Y) compared to other independent variables (X1, X2) at High School Of High School Al-Falah Sumber Gayam Kadur Pamekasan Madura.